2016
DOI: 10.1080/00014788.2016.1192985
|View full text |Cite
|
Sign up to set email alerts
|

Do corporate tax cuts increase investments?

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 51 publications
2
28
1
1
Order By: Relevance
“…This suggests that the tax cuts from the relatively high level of tax rate could provide large impacts on investment of local firms. This finding is consistent with that of Dobbins and Jacob (2016) are consequently likely to exhibit stronger investment response.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…This suggests that the tax cuts from the relatively high level of tax rate could provide large impacts on investment of local firms. This finding is consistent with that of Dobbins and Jacob (2016) are consequently likely to exhibit stronger investment response.…”
Section: Resultssupporting
confidence: 90%
“…There is, however, a relatively limited empirical evidence on the effects of direct cut in the statutory tax rate, especially that of the developing world. Dobbins and Jacob (2016), for example, shows that the German tax rate cut has a strong impact on investment of local firms. This represents an important gap in the literature since studies have shown that the tax sensitivity could vary with the country's development level (see, for example, Mutti and Grubert 2004) and the cuts in the corporate tax rate have been proposed in many developing countries as a way to boost private investment.…”
Section: Introductionmentioning
confidence: 99%
“…Since the beginning of the 21st century, there has been significant changes in national corporate income tax rates worldwide. The underlying reason for these changes is that countries aspired to attract investment and stimulate business growth, which has resulted in a major trend toward decreasing the tax rates that firms pay for their profits (Dobbins and Jacob 2016). For example, the average corporate tax rate (CTR) was 30.42 percent in 2000 and 22.43 percent in 2017 for the Organisation for Economic Co-operation and Development (OECD) member countries.…”
Section: Introductionmentioning
confidence: 99%
“…Tax rebates are policy incentives that encourage green investment activities, and they decrease tax liability and the financing costs of green investment activities (Dobbins & Jacob, 2016; Maffini et al, 2019; Tian, 2018). Third, government subsidies and tax rebates are beneficial market signals that imply better investment prospects and higher profitability for external investors (Chen et al, 2018; Wu, 2017).…”
Section: Theoretical and Hypothesis Analysismentioning
confidence: 99%
“…Private family firms avoid taxes less than public family and nonfamily firms (Brune et al, 2019). Tax cuts and credits generate an important impact on firm investments and capital allocation (Altug et al, 2009; Ayuso et al, 2018; Danielova & Sarkar, 2011; Dobbins & Jacob, 2016; Haga et al, 2019; Hines & Park, 2019; Marekwica, 2012; Muthitacharoen, 2021; Sarkar, 2012). Payout and repatriation taxes have a large impact on firm investment activity (Becker et al, 2013; Hanlon et al, 2015).…”
Section: Introductionmentioning
confidence: 99%